2016
DOI: 10.1111/glob.12127
|View full text |Cite
|
Sign up to set email alerts
|

Rethinking migration in the digital age: transglocalization and the Somali diaspora

Abstract: In this study, we examine the transnational networks of the Somali diaspora online. We explore the claims that the web signifies a shift towards a de‐territorialized, transnational diaspora, which constructs its identity and engagement around a transnational imagined community. Based on a network and web content analysis, we assert that the claims about the transnational as the territorial locus of identity and engagement should be revisited. The analysis shows that the Somali diaspora's engagement has a speci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
61
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
5
3
2

Relationship

0
10

Authors

Journals

citations
Cited by 50 publications
(66 citation statements)
references
References 46 publications
3
61
0
Order By: Relevance
“…Adamson and Koinova (2013) have also shown that London as a global city provides a specific space for diasporas to mobilise with the clustering of institutions, networks, and resources conducive for diaspora mobilisation. More recently scholarship has started growing from different directions and scholarly networks to show that diasporas mobilize beyond a classic triangular relationship model considering interactions between host-states, home-states, and diasporas, but do so in a variety of spaces, such as cities, online, refugee camps, supranational organizations, sites of global visibility, and spaces contiguous or distant from the homeland (Brinkerhoff 2009;Adamson 2016;Brkanic 2016;Gabiam and Fiddian-Qasmiyeh 2016;Kok and Rogers 2016;Van Hear and Cohen 2017;Koinova and Karabegovic 2017;Koinova 2018). Some of these scholars have built on works emphasising the effects of space, place, scale, and positionality (Johnston 1973;Lefebvre 1974;Sheppard 2002;Brenner 2004;Sassen 2007;Herod 2011), which have preoccupied geography scholars for several decades.…”
Section: Focus On Context: Spatial and Temporal Dimensionsmentioning
confidence: 99%
“…Adamson and Koinova (2013) have also shown that London as a global city provides a specific space for diasporas to mobilise with the clustering of institutions, networks, and resources conducive for diaspora mobilisation. More recently scholarship has started growing from different directions and scholarly networks to show that diasporas mobilize beyond a classic triangular relationship model considering interactions between host-states, home-states, and diasporas, but do so in a variety of spaces, such as cities, online, refugee camps, supranational organizations, sites of global visibility, and spaces contiguous or distant from the homeland (Brinkerhoff 2009;Adamson 2016;Brkanic 2016;Gabiam and Fiddian-Qasmiyeh 2016;Kok and Rogers 2016;Van Hear and Cohen 2017;Koinova and Karabegovic 2017;Koinova 2018). Some of these scholars have built on works emphasising the effects of space, place, scale, and positionality (Johnston 1973;Lefebvre 1974;Sheppard 2002;Brenner 2004;Sassen 2007;Herod 2011), which have preoccupied geography scholars for several decades.…”
Section: Focus On Context: Spatial and Temporal Dimensionsmentioning
confidence: 99%
“…Such digital methods approaches have been successful in producing digital representations of national and religious diasporas' online presences in what appear to be comprehensive visual records; one example is Kok and Rogers's (2016) work on the Somali diaspora. However, these visualizations offer a series of snapshots that produce partial, static visual accounts of a socio-cultural phenomenon that constructivist theorizations of diaspora have defined as a continuous and layered formation process.…”
Section: Operationalizing Digital Diasporamentioning
confidence: 99%
“…Alongside building the important open-source network visualization tool Gephi, 3 they offer interactive graphical visualizations of the corpus, in addition to archiving raw qualitative empirical open data such as texts, videos, interviews gathered in the research. Kok and Rogers (2017) queried local domain search engines (google.co.uk, .nl, co.ke, .se, .dk, .no, .ca and .com) for Somali diaspora related keywords and imported search results in IssueCrawler, a network visualization tool. 4 They also queried Facebook in the search box for pages of self-identifying Somali groups, the search result pages were "liked" in order to be able to extract data from these pages using the Facebook research tool Netvizz.…”
Section: Paradigm (Iii) Migrants As Datamentioning
confidence: 99%